2021
DOI: 10.1186/s13068-021-01989-9
|View full text |Cite
|
Sign up to set email alerts
|

MdFRK2-mediated sugar metabolism accelerates cellulose accumulation in apple and poplar

Abstract: Background Cellulose is not only a common component in vascular plants, but also has great economic benefits for paper, wood, and industrial products. In addition, its biosynthesis is highly regulated by carbohydrate metabolism and allocation in plant. MdFRK2, which encodes a key fructokinase (FRK) in apple, showed especially high affinity to fructose and regulated carbohydrate metabolism. Results It was observed that overexpression of MdFRK2 in ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…LRR , UGT , LAC , DUF247 and TCP11 genes were found to be closely related to the transition from primary growth to secondary growth. Among them, LAC and UGT genes were closely related to lignin formation [ 32 , 66 , 67 ]. Interestingly, AtDUF247 was expressed particularly in vascular and developing tissues, which was necessary to maintain normal cell wall composition and structure by affecting the expression of other gene members in Arabidopsis [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LRR , UGT , LAC , DUF247 and TCP11 genes were found to be closely related to the transition from primary growth to secondary growth. Among them, LAC and UGT genes were closely related to lignin formation [ 32 , 66 , 67 ]. Interestingly, AtDUF247 was expressed particularly in vascular and developing tissues, which was necessary to maintain normal cell wall composition and structure by affecting the expression of other gene members in Arabidopsis [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLE and SCL are associated with cellulose synthesis [ 76 , 77 ], CESA6 which closely related to primary wall also mainly expressed in primary growth stage [ 78 , 79 ]. UDP and UGT are related to hemicellulose synthesis were also explore [ 66 , 67 ]. While PttEXP1 gene was more active in the secondary growth of mature stem segments [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of metabolism was involved in the formation of tuber wounds, among which, sugar metabolism, phenylpropanoid metabolism, and fatty acid biosynthesis played an important role in the formation of wounds ( Schmutz et al, 1996 ; Graca and Pereira, 2000a ; Su et al., 2021 ). We found that low-temperature treatment suppressed sugar metabolism in tubers, which may inhibit the supply of energy and precursor substance during healing ( Su et al., 2021 ). StAMY23 and StBAM1 play distinct roles in starch degradation, particularly under cold conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sugar serves as an energy and carbon source for lignin and suberin synthesis in plants ( Su et al., 2021 ). The evidence from published studies reveals that sucrose formed in the leaves of potato tubers during the ripening process can be transported to potato tubers and then transformed into starch for storage.…”
Section: Introductionmentioning
confidence: 99%
“…We still do not know whether it was related to the sugar metabolism or signaling pathway. Several sugarmetabolism-related genes, exemplified by the MdFRK2 (Su et al, 2021) and phosphoenolpyruvate carboxykinase (PEPCK) (Osorio et al, 2013), were reported to be directly linked to the sugar accumulation of plants.…”
Section: Fphxk1 Impacts Sugar and Secondary Metabolism In Strawberry ...mentioning
confidence: 99%